2008
DOI: 10.1021/bi800912w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Incompetence of Synemin Is Related to the Property of Its Head and Rod Domains

Abstract: The mechanisms regulating the intermediate filament (IF) protein assembly are complex and not yet fully understood. All vertebrate cytoplasmic IF proteins have a central alpha-helical rod domain flanked by variable head and tail domains. The IF protein synemin cannot homopolymerize to form filament networks; it needs an appropriate copolymerization partner. To elucidate the roles of the vimentin head domain, the TAAL motif in the 2A region, and the TYRKLLEGEE motif in the 2B region of the rod domain in synemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Synemin is present in two alternatively spliced forms, ␣ and ␤. Previous studies revealed synemin at different subcellular locations in cardiac and skeletal muscle, neurons, and glial cells (18,21,25,28,31) and showed that synemin interacts with several other proteins, including desmin, vimentin, ␣-actinin, and vinculin (14,20,21,25), which all bind to the ␤ isoform, with additional binding sites for vinculin and talin on ␣-synemin (26,27). Here we test the hypothesis that both isoforms of synemin are expressed in the developing heart and that each isoform associates with and differentially stabilizes distinct structures in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synemin is present in two alternatively spliced forms, ␣ and ␤. Previous studies revealed synemin at different subcellular locations in cardiac and skeletal muscle, neurons, and glial cells (18,21,25,28,31) and showed that synemin interacts with several other proteins, including desmin, vimentin, ␣-actinin, and vinculin (14,20,21,25), which all bind to the ␤ isoform, with additional binding sites for vinculin and talin on ␣-synemin (26,27). Here we test the hypothesis that both isoforms of synemin are expressed in the developing heart and that each isoform associates with and differentially stabilizes distinct structures in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Highly expressed in adult skeletal and cardiac muscle (13,14), synemin is also found in smooth muscle, neurons, glial cells, and hepatic stellate cells (15,18,19). In myocytes, synemin integrates into filaments containing desmin or vimentin via its rod domain (14,20,21). The rod domain of synemin can also interact with keratins 5 and 6 (22) (although these have not been identified in striated muscles) and 3 components of the dystroglycan complex: dystrophin, utrophin (23), and ␣-dystrobrevin (24).…”
mentioning
confidence: 99%
“…Synemin is unique in that it cannot homopolymerise to form filament networks, and therefore requires an appropriate copolymerisation partner, such as desmin, vimentin or keratin, depending on the cell type, to form filamentous structures (Bellin et al, 1999;Chourbagi et al, 2011;Hirako et al, 2003;Khanamiryan et al, 2008). Consequently, synemin filaments are unstable and delocalised in the cells of mice lacking desmin or vimentin (Carlsson et al, 2000;Izmiryan et al, 2006;Izmiryan et al, 2009;Jing et al, 2007;Xue et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The two larger isoforms of synemin (H and M) harbor extended C-terminal tails that project from the surface of the filament and provide connecting arms that associate with neighboring proteins [5-7]. In contrast, the small isoform (L) lacks this tail domain [3,8]. …”
Section: Introductionmentioning
confidence: 99%